1875–1876 Ala. Acts 46, Rev. Code, ch. 1, § 1(5) - (:unkn) unknown (General Publisher, 1875)
Imposed $50 occupational tax on dealers of pistols, Bowie knives, and dirk knives.
--
Keywords: TAX - DEALERS